COMMUNITY DEVELOPMENT THROUGH VILLAGE PARIGI LOCAL RESOURCE UTILIZATION - Agustinus, Candra (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Activity Real Working Lecture (KKN) Faculty of Islamic economy in 2016 is one manifestation of Panca Dharma College University Djuanda namely Community devotion. As for the object of corruption are the 2016 FEI Society Kp. Parigi Tangkolo Rural Development theme Kabandungan with Sharia-based economic activity. No action whithout goal. Therefore, the purpose of the Student FEI KKN is to be a facilitator for the community in solving social and economic problems by optimizing natural resources and human resources, especially people in the Kp. Tangkolo Parigi. Results of the 2016 FEI corruption can be simply summed have found the local potential in the natural surroundings and take positive action against such potential, namely the processing of agricultural products and the field of nature conservation eggplant. Hopefully, by the development of the processing of agricultural products, we can improve the HDI (Quality Performance Index) especially components perekonomi surrounding communities.